Spatial Dependence Structure of Total Factor Productivity in Polish Local Administrative Districts - Ciołek, Dorota; Brodzicki, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The interaction between space (location) and the processes of accumulation (growth) is one of the most interesting and at the same time the most difficult areas of modern economic theory. The up till now empirical research on determinants of regional productivity in the case of Poland is however relatively scarce. Most studies focus on explaining the variation in regional income per capita mostly at NUTS–2 and NUTS–3 levels, and only a few take into account a highly spatially disaggregated NUTS–4 level. We aim to fill this important gap. The present article has several objectives. We try to explain the spatial patterns of productivity, to identify the spatial range of productivity spillovers empirically and to identify the determinants of the Total Factor Productivity (TFP) growth in Poland with the use of spatial econometric modeling and the extended version of the Nelson‑Phelps (1966) model. The study adopts an NUTS-4 level of local administrative districts (powiats) which we find superior on both theoretical (market closing) and empirical grounds (spatial modeling). TFP in Poland assumes the highest values in the metropolitan centers and spreads out on their nearest surroundings with the maximum value for Warsaw. The secondary local hills in TFP are located in cities or towns with county rights. TFP, in general, shows a downward trend as one moves from the west to the east with the lowest values observed in the south‑eastern part of Poland. The range of TFP spillover is found to be of roughly 175–200 km and is nonlinearly decreasing from the local productivity hills. Furthermore, the rate of growth of TFP shows spatial autocorrelation and is found to depend positively on the rate of increase in human capital endowment and on the gap from the leader under certain assumptions. We find no evidence of the channel through imports. However, the FDI channel is found to be robust and strong.